Pengaruh Latihan Resistance Band Dan Balance Board Terhadap Tendangan Dwi Hurigi Pada Atlet Warrior Taekwondo Club Kota Palopo - Aswandi Aswandi; A. Heri Riswanto; Rachmat Hidayat (Universitas Hamzanwadi, 2026)
The double hurigi kick, as a complex taekwondo technique, requires explosive power and dynamic balance, but is often difficult for adolescent athletes to perform. This study aims to analyze and compare the effectiveness of resistance band and balance board training on improving double hurigi kicking ability. Using a quasi-experimental method with a pretest-posttest two-group design, the sample consisted of 20 Warrior Taekwondo athletes aged 13-17 years who were divided into two groups. The intervention was conducted for 8 weeks with a frequency of 3 times per week, and the research instrument was a dwi hurigi kick accuracy test within 30 seconds. The data were analyzed using a paired sample t-test and an independent sample t-test. The results showed a significant improvement in both groups. The resistance band group experienced an average increase of 3.40 points (Cohen's d = 4.86), while the balance board group increased by 2.00 points (Cohen's d = 3.00). Intergroup comparison analysis showed a significant difference (p = 0.029) with resistance band training having the advantage. Discussion revealed that resistance bands were more effective because they specifically increased the rate of force development and optimized the stretch-shortening cycle, which is essential for explosive kicks. It was concluded that although both were effective, resistance band training was significantly superior in improving double kick performance in adolescent taekwondo athletes.